A DC-DC converter for internet-of-things power management IC - Lim, Jian Wen (2017)
The Internet of Things (IoT) is set to explode in the foreseeable future with devices with integrated sensing, computation and communication capabilities that are operated in a low- power mode for most of their operation to extend the limited battery life. This creates challenges for power management circuits which will supply the micro-ampere sleep mode currents. They are high conversion efficiency at these sleep mode currents and low quiescent current operation of the converter. The implementation should also use less silicon area for implementation in small IoT devices. This project would explore and study techniques used by existing DC-DC converters to improve their efficiency in the sleep mode also known as light load conditions, methods to reduce quiescent current during operation and how to maintain high efficiency across the wide load ranges expected in IoT devices. A review of the principles behind the design of buck converters is also included. These methods were implemented successfully into a buck converter which achieved high conversion efficiency of 80% at a load current of 50 µA with the quiescent current measured to be 7 µA converting 2.4 V to 1.8 V with a maximum peak voltage ripple of 27.7 mV which is about 1.5% of 1.8V in the simulator results.